Financial Transactions Tax : Panacea, Threat, or Damp Squib? - Honohan, Patrick (World Bank, 2013)
The authors argue that attempts to raise a significant percentage of gross domestic product in revenue from a broad-based financial transactions tax are likely to fail both by raising much less revenue than expected and by generating far-reaching changes in economic behavior. They point out that, although the side effects would include a sizable restructuring of financial sector activity, this would not occur in ways corrective of the particular forms of financial overtrading that were most conspicuous in contributing to the crisis. Accordingly, such taxes likely deliver both less revenue and less efficiency benefits than have sometimes been claimed by some. On the other hand, they may be less damaging than feared by others.